Discovering the global landscape of problem-based learning and critical thinking: a bibliometric review - Yogalingam Subramaniam; Muzirah Musa (Journal of Education and Learning (EduLearn), 2026)
This study seeks to explore recent trends in publications related to problem-based learning (PBL) and critical thinking (CT). It analyzes annual growth rate, document type, source, languages, and subject area to assess their impact. This study identified publications by countries, analyzed authorship, and highlighted the most active institutions. It examined prevalent PBL and CT themes by analyzing keyword occurrences, source titles, and abstracts. A bibliometric approach was used to map existing research on PBL and CT from the Scopus database. The data were analyzed through the VOSviewer software for data visualization, Microsoft Excel 365 for frequency analysis, and Herzing’s Publish or Perish software for citation metrics. The findings demonstrated a growing combination of PBL and CT with an increasing demand. Articles, journals, English, and social sciences were the increasing types of publication documents (TP). The United States published the most documents. Donnelly, J. from Three Rivers Community was the top researcher in PBL and CT publications. Hong Kong Polytechnic University had the highest average citations per publication. The keyword “PBL” was frequently employed, and nursing education journals significantly impacted PBL and CT publications. Simultaneously, engineering and thinking skills were frequently employed terms in the title abstract and title field.